Vitrification of male gametes — our experience - Gaydarova, Lora; Hristova, Elena; Todorov, Plamen (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):231